[Portuguese translation] Using Science to Inform Heat Mitigation: From Organizational Planning to Individual Action - Hosokawa, Yuri (2026)
As rising global temperatures increase heat-related risks, effective heat mitigation requires coordinated actions at both organizational and individual levels. This editorial highlights three recent studies that provide evidence-based approaches to protecting physically active individuals in hot environments. Organizational strategies include event planning, medical preparedness, stakeholder coordination, and emergency response systems for mass sporting events. Individual-level tools can improve decision-making by integrating environmental conditions, activity characteristics, and personal factors to guide hydration, cooling, clothing, and activity modifications. Evidence also suggests that water-resistant sunscreen may slightly elevate core body temperature during exercise in the heat. Together, these studies demonstrate that comprehensive, multi-level strategies are essential for reducing heat-related illness and translating scientific evidence into routine practice.